Species diversity and distributions of microdrile earthworms (Annelida, Clitellata, Enchytraeidae) from South America - Christoffersen, Martin L. (Zootaxa, 2009)
A comprehensive biodiversity database of Enchytraeidae produced 66 nominal species reported to date from South America (Achaeta, 6 species; Buchholzia, 1; Cognettia, 1; Enchytraeus, 3; Fridericia, 5; Grania, 1; Guaranidrilus, 10; Hemienchytraeus, 12; Henlea, 2; Lumbricillus, 7; Marionina, 12; Stephensoniella, 1; Timmodrilus, 1; Tupidrilus, 4). Almost 76% of this fauna (50 species) is endemic to the South American continent. The remaining 16 species are more or less largely distributed. Detailed South American occurrences are provided. This is the first reassessment of South American enchytraeids in 27 years. The group is conspicuoulsy absent from the northeast region of Brazil. Enchytraeidae are microdrile earthworms, representing the sister group of the Crassiclitellata, or megadrile earthworms. This relationship is supported by molecular phylogenies, ontogenetic transformations, ecological evidence, and several morphological synapomorphies (dorsal pores, contractil dorsal vessel, lateral position of dorsal chaetal bundles, and shape of chaetae).